Validation of names of some syntaxa of the Fagetalia sylvaticae from Ukraine - Onyshchenko, V.A. (Український ботанічний журнал, 2017)
The names of alliance Scillo sibericae-Quercion roboris (deciduous mesic forests of Eastern Europe on rich soils in Forest-Steppe and Steppe regions), associations Stellario holosteae-Fagetum, Euonymo verrucosae-Fagetum, Anthrisco nitidiAceretum pseudoplatani, Tulipo quercetorum-Quercetum roboris and 10 subassociations are validated.